KETERAMPILAN MENULIS DESKRIPSI SEKOLAH DASAR KELAS TINGGI MENGGUNAKAN MODEL PEMBELAJARAN KONTEKSTUAL - Andreas Ivan; Ronny Mugara; Ryan Dwi Puspita (IKIP Siliwangi, 2022)
This study examines the application of a contextual learning model. The purpose of this study was to determine the application of the contextual learning model to improve the writing skills of descriptive essays in high grade elementary school students. This research is motivated by several problems experienced by students in writing descriptive essays. This study uses a literature review method, with the aim of describing the ability to write descriptions of high-grade elementary school students using a contextual learning model. The data was collected by tracing the Sinta indexed electronic National journal. From the results of this study, 5 relevant articles showed that the writing skills of students' description essays increased based on cycle 2 which reached 80%. Thus it can be concluded that the skills of writing essays of descriptions of students improve by using contextual learning models in high grade elementary school students.